RISIKO PENGELOLAAN KAWASAN PERBATASAN NEGARA DENGAN MODEL KERJA SAMA EKONOMI INTERNASIONAL - Zulkifli, Abdul Latif, Rise Karmilia (Jurnal Ilmiah Cano Ekonomos, 2017)
Areas along land borders Indonesia today there are many people who do not prosperous, it is because most of the land area that borders Indonesia is still limited management procedures for administrative purposes, not to use the concept of international economic cooperation. The purpose of the study tries to explain the implications of the management of the border region through economic cooperation at the border of the provisions of the legislation in Indonesia, as well as the implementation of economic cooperation concepts like what is appropriate. Normative research was conducted through library research to obtain secondary data, comprised of both legal materials and primary and secondary tertiary legal materials. Secondary data collected from the research literature were analyzed using a qualitative approach. The research concludes that international economic cooperation should be based on the potential advantages of the border area so as to improve the welfare of border communities without harmfull nation sovereignty